Seed rate and row spacing effect on yellow sarson (Brassica rapa var. trilocularis) under rainfed conditions: Seed rate and row spacing effect on yellow sarson (Brassica rapa var. trilocularis) under rainfed conditions - K THAKURIA; C THAKURIA (Journal of Oilseeds Research, 2014)
A field experiment was conducted during rabi season of 2010-11 at Assam Agricultural University, Jorhat to study the effect of four seed rates (4, 6, 8 and 10 kg/ha) and two row spacings (30 and 40 cm) on the productivity of yellow sarson. Increasing the seed rate from 4 to 10 kg/ha increased the growth, yield attributes and yield of yellow sarson, however, the differences among the seed rates 6, 8 and 10 kg/ha were not significant. Out of the two row spacings, the closer row spacing of 30 cm recorded significantly higher seed yield and harvest index over the wider row spacing of 40 cm. The oil content was not affected significantly due to different seed rates and row spacings.